Sarup kh̨ōmūn Mahātthai chut kh̨ōmūn ch̄œng nayōbāi samrap phūb̨ōrihān radap sūng (Sūn Sarasonthēt, Samnakngān Palat Krasūang Mahātthai, Krasūang Mahātthai, 1997)
Statistics of Ministry of Interior, Thailand.